The Effect of Strategic Orientation Through Social Capital on the Performance of the Republic of Indonesia Public Employee Cooperative (KPRI) Tulungagung Regency - Sawal Sartono; U Ujianto; Tri Andjarwati (Athena: Journal of Social, Culture and Society, 2024)
Strategic orientation refers to how organizations should interact with customers, competitors, technology, and other external factors to make optimal strategic choices. Research using four orientations simultaneously is still rarely done and given the importance of social capital in social enterprises, this study will analyze the effect of social capital as an intervening variable on the performance of KPRI. Based on this, this study aims to determine the effect of strategic orientation on KPRI performance with social capital as an intervening variable. The research method uses quantitative methods with path analysis and data analysis using the PLS Smart application. The results of the study resulted in the following findings; Entrepreneurial orientation. Market orientation Technology orientation has no effect, learning orientation has no effect on KPRI performance. Social capital has a significant influence on the performance of KPRI in Tulungagung Regency. Social capital is proven as an intervening variable affecting entrepreneurial orientation, market orientation, technology orientation, learning orientation on KPRI performance. KPRI management is more risk averse to maintain financial balance so that the social mission of the cooperative is maintained. The majority of KPRI's business is savings and loans, KPRI members to meet urgent financial needs prefer to borrow from KPRI. The use of technology and learning orientation is still limited due to constraints on KPRI's resources. Improving cooperative performance can be done by the management by strengthening social capital in KPRI.